1985 LEGISLATIVE SEMINAR THE GREENBRIER (Tufts Archival Research Center, 2007)
Confidential; Missing Page(s); Speech by Tobacco Institute Senior Vice President Roger Mozingo at the 1985 Legislative Counsel Meeting. Reviews the challenging issues faced by the Tobacco Institute in 1985 including: excise taxes, smoking restrictions, "self-extinguishing" legislation, and product liability legislation. Reviews several defeats of anti-tobacco legislation in 1985.